EVALUATION OF RELIABILITY AND EFFICIENCY OF ELECTRONIC MEDICAL SYSTEMS FUNCTIONING - S. M. Borovikov; I. N. Tsyrelchuk; S. S. Dick; N. N. Tsyrelchuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A new approach to the evaluation of the functioning of the electronic systems for medical purposes is proposed. This approach takes into account the sustainable system failures and possible temporary system device failures due to the impact of their work of natural and industrial influences.